Do climate policy uncertainty and economic policy uncertainty promote firms' green activities? Evidence from an emerging market - Nguyen Thi Hoa Hong; Pham Tuan Kien; Ha Gia Linh; Nguyen Vu Ha Thanh; Nguyen Le Tuan; Phung Duc Anh (Cogent Economics & Finance, 2024)
This study examines the joint effects of climate policy uncertainty (CPU) and economic policy uncertainty (EPU) on the green activities (GAs) of Vietnamese listed companies from 2010 to 2022. CPU and EPU are measured by standardizing the search volume index of relevant keywords using data from Google Trends and Glimpse. Meanwhile, GAs are assessed through variables related to green finance (GF) and green innovation (GI). The findings from multivariate regression models show a positive relationship between CPU, EPU, and either GF or GI in Vietnam during the period of 2010-2022. Furthermore, the interaction between CPU and EPU positively influences both GF and GI among listed firms throughout the research period. This study suggests that governments promoting policies to enhance economic activity or address climate change can facilitate firms in sustaining their green economic activities.
Keywords: G32; G38; Q01; 330; Climate policy uncertainty; economic policy uncertainty; green activities; green finance; green innovation